Strategic Innovation Development Based on Systems Research in a Rural Region - Sarkkinen, Minna; Kässi, Tuomo (International Journal of Industrial Engineering and Management, 2013)
Strategic thinking is required to account for the different dimensions of strategic innovation management.The study builds and analyses three viewpoints of strategic innovation management, i.e. innovation environment, value delivery and innovation capability, in the context of a regional innovation system. The aim is to study how the different dimensions describe innovation situation and development needs in firms and at regional level. The data for the study was collected during 2011 in a remote rural region located in Finland. The logic of purposeful sampling was used in the selection of the 50 firms. Soft systems methodology is applied as a systems research methodology and exploratory factor analysis is used as a method to analyze the three dimensions. The findings of the study identify several factors forming the three dimensions, which may have structural connection with each other. The factors highlight, e.g. the importance of networking capability and marketing related goals of innovation. Article history: Received (06 February 2013); Revised (20 May 2013); Accepted (27 May 2013)